QUALITY OF HEALTH INSURANCE SERVICES FOR THE POOR (JKMM): A CASE STUDY OF THE PORONG DISTRICT PUBLIC HEALTH CENTER, SIDOARJO REGENCY - Nofiro Bening Dwi Wangakasa Bening; Singgih Manggalou (SOSIOEDUKASI, 2026)
Opulation growth and increasing demand for health services have prompted Sidoarjo Regency to increase the capacity of its health system, especially for the poor who most need access to health services. Poor communities experience relatively difficulty in accessing health facilities due to limited medical costs, while not all are covered by the Premium Assistance Recipient (PBI) program funded by the central government. Therefore, in addition to the PBI program, the Sidoarjo Regency Government also implements the Poor Community Health Insurance Program (JKMM) as a form of protection and social security for poor communities not covered by PBI. This program applies specifically to Sidoarjo residents and one of its implementations is at the Porong Community Health Center. By increasing public understanding of health service rights, it is hoped that the poor can maximize service utilization. This study aims to analyze the quality of the Poor Community Health Insurance (JKMM) service at the Porong Community Health Center in Sidoarjo Regency. This study used descriptive qualitative method using the service quality theory according to Zeithaml et al. as cited by Hardiansyah (2018). This study proves quality of JKMM services at the Porong Community Health Center has been good, although evaluation and guidance from the government are still needed to minimize obstacles and ensure optimal service delivery.